Analisis Kesesuaian Lahan Untuk Tempat Evakuasi Akhir (TEA) Bencana Tsunami di Kecamatan Sirimau - Fazlur Fardhian Isa Kaplale; Ferad Puturuhu; Rifyan Ruman (Jurnal Pendidikan Geografi Unpatti, 2025)
The Sirimau subdistrict is one of the areas in Ambon City that has a high level of tsunami threat due to its location on the coast and in an active tectonic zone. The purpose of this study is to analyze the suitability of final tsunami evacuation sites based on several variables such as elevation, disaster vulnerability, land use, carrying capacity, and accessibility. The method used in this study is spatial analysis using a GIS-based overlay approach. The results of this study indicate that not all available locations meet the criteria for suitability as final evacuation sites. Based on the overlay and spatial analysis results, several ideal locations were identified for development as evacuation sites. This study provides recommendations for priority locations and strategies that can be used to enhance the preparedness and safety of the Sirimau District community from tsunami threats.